Humans in Digitized Worlds: Perspectives on Self-Expansion, Outdoor Activities, and Body Perception - André Klostermann (Current Issues in Sport Science)
The growing influence of digital media has fundamentally transformed human experience, particularly in relation to physical activity and self-perception. As digital worlds increasingly permeate our daily lives, it becomes essential to examine how these technologies shape our interactions with the environment, our bodies, and our sense of self. This symposium seeks to explore these intersections, highlighting how digital worlds shape our embodied experiences and self-perception. The first presentation examines the philosophical implications of wearable fitness technologies, focusing on how self-tracking devices influence self-knowledge and create potential dissonance between digital feedback and bodily awareness. The second explores the role of digital tools in outdoor activities, presenting a framework to understand their impact on the relationship between humans and nature. The third turns to adolescence, investigating how social media use and physical activity affect body image and interoception. Together, these contributions offer a multidisciplinary perspective on bodies and digital media.